GENDER EQUALITY IN THE FAMILY: STEREOTYPES AND FACTS - Dilnavoz Ozodovna Tadjibaeva (PT. Antis International Publisher, 2025)
Objective: This study examines gender equality within the family in Uzbekistan, focusing on the persistence of gender stereotypes and their impact on social dynamics. It also investigates the implications of selective abortion on demographic balance. Method: The research employs a qualitative approach, analyzing policy documents, demographic data, and cultural narratives to assess the intersection of gender norms and legal reforms. Results: Findings indicate that while Uzbekistan has made significant progress in aligning gender policies with international standards, deeply ingrained cultural stereotypes continue to hinder women’s full participation in various spheres of life. Additionally, selective abortion has contributed to a demographic imbalance, raising concerns about long-term socio-economic consequences. Novelty: This study provides a critical analysis of gender inequality within the framework of national traditions and state policies, offering insights into the socio-cultural barriers to achieving gender parity in Uzbekistan. By highlighting the intersection of policy and societal norms, the study contributes to discussions on sustainable gender reforms and demographic challenges.